Ultralong α-MoO3 nanobelts : synthesis and effect of binder choice on their lithium storage properties - Wang, Zhiyu (2013)
Ultralong α-MoO3 nanobelts with an average length of 200–300 μm and uniform width of around 0.6–1.5 μm have been synthesized by a facile hydrothermal method using a molybdenum organic salt precursor. When evaluated for their lithium storage properties, the composite electrodes made from these nanobelts and bioderived polymer binders containing carboxy groups exhibit much better electrochemical performance than that composed of conventional poly(vinylidene fluoride) (PVDF) binder. Remarkably, the electrodes using sodium carboxymethyl cellulose (Na-CMC) binder can deliver the high specific capacity of over 730 mA h g–1 for over 200 cycles at a 0.2 C rate. Even cycled at high rates of 1–2 C, high capacities of around 430–650 mA h g–1 can be still retained. The positive effect of this type of binder on the electrode properties of α-MoO3 nanobelts is further evidenced by using another bioderived binder, the sodium alginate (Na-alginate). Stable capacity retention of around 800 mA h g–1 for over 150 cycles at 0.2 C well-demonstrates that the choice of binder can greatly influence the electrochemical performance of metal oxide electrodes, especially those suffering from large volume expansion upon lithium intake.